Chemical composition of oil palm extractives. - H. Simatupang, Maruli (1994)
Air dry meal of oil palm trunk was successively extracted (yields in brackets are based on oven dry oil palm trunk material) with petroleum ether (0.15%); ethyl ether (0.3%); acetone/water ratio 9:1 (3.3%);ethanol water ratio 9:1 (3.9); and hot water (1.1%) .. The petroleum ether extracts were fractionated into free acids (0.0315%) and neutral parts .. (0.1185%).